The incidence of sarcopenia among hospitalized older patients: results from the Glisten study - Martone, Anna Maria; Bianchi, Lara; Abete, Pasquale; Bellelli, Giuseppe; Bo, Mario; Cherubini, Antonio; Corica, Francesco; Di Bari, Mauro; Maggio, Marcello; Manca, Giovanna Maria; Marzetti, Emanuele; Rizzo, Maria Rosaria; et al. (Journal of cachexia, sarcopenia and muscle, 2017)
Background New evidence is emerging on the importance of lean body mass during periods of illness and recovery. The preservation of lean body mass during such periods of intense stress impacts both patient and treatment outcomes. However, data concerning the incidence of sarcopenia among older people during hospitalization are scarce. The objective of this study was to evaluate the development of sarcopenia in a sample of hospitalized older subjects. Methods We used data of 394 participants from the multicentre Italian Study conducted by the Gruppo Lavoro Italiano Sarcopenia—Trattamento e Nutrizione (GLISTEN) in 12 Acute Care Wards (Internal Medicine and Geriatrics) of University Hospitals across Italy. This study was designed to determine the prevalence of sarcopenia at hospital admission and the change in muscle mass and strength during hospitalization. Sarcopenia was defined as low skeletal mass index (kg/m2) along with either low handgrip strength or slow walking speed [European Working Groups on Sarcopenia in Older People (EWGSOP) criteria]. Estimation of skeletal muscle mass was performed by bioelectrical impedance analysis (BIA). Results The mean age of the 394 enrolled patients (including 211 females who accounted for 53% of the sample) was 79.6 ± 6.4 years. Among those without sarcopenia at hospital admission, 14.7% of the study sample met the EWGSOP sarcopenia diagnostic criteria at discharge. The incidence of sarcopenia during hospitalization was significantly associated with the number of days spent in bed but was not correlated with the total length of hospital stay. In particular, patients who developed sarcopenia spent an average of 5.1 days in bed compared with 3.2 days for those with no sarcopenia at discharge (P = 0.02). Patients with sarcopenia showed a significantly lower body mass index compared with non‐sarcopenic peers (25.0 ± 3.8 kg/m2 vs. 27.6 ± 4.9 kg/m2, respectively; P < 0.001). Similarly, the skeletal mass index at admission was significantly lower among patients who developed sarcopenia during hospital stay. Conclusions Incident sarcopenia during hospital stay is relatively common and is associated with nutritional status and the number of days of bed rest.